Highly efficient fluorene/indole-based hole transport materials for green PhOLEDs. (March 2019) - Wu, Panpan; Song, Wenxuan; Xia, Zhenyuan; Chen, Yi; Tian, Guojian; Huang, Jinhai; Su, Jianhua
Abstract: Three hole transport materials, FIPN- p -PCz, FIPN- p -TPA and FIPN-DPCz, incorporating fluorene/indole core with carbazole or triphenylamine unit were synthesized and fully characterized. The photophysical properties, thermal properties and electrochemical properties of these three compounds were fully investigated. The FIPN-based hole transport materials show high thermal stability (Td  > 420 °C) and appropriate highest occupied molecular orbital (HOMO) level (∼-5.2 eV). Green phosphorescent organic light-emitting diodes (PhOLEDs) using these FIPN-based derivatives were fabricated to investigate the device performance, compared with NPB as the reference hole transport material. It turned out that the devices using these three compounds exhibited superior performance than that of the NPB-based PhOLED device. Especially, the FIPN- p -PCz based device showed outstanding electroluminescence performance with the maximum current efficiency and external quantum efficiency of 53.7 cd/A and 17.3%, respectively, which was almost twice that of the NPB based device. Graphical abstract: Highlights: The research was based on indole and fluorene, which is excellent hole transport moieties. The three synthesized compounds possess high thermal stabilities, which can be used in OLED stably. The OLEDs based on the three synthesized materials indicated much higher efficiency than NPB in the same device structure.